Ocular Manifestations of a Novel Proximal 19p13.3 Microdeletion. (30th April 2018) - Swan, L.; Coman, D.
Abstract : Microdeletions at 19p13.3 are rarely reported in the medical literature with significant phenotypic variability. Among the reported cases, common clinical manifestations have included developmental delay, facial dysmorphism, and hypotonia. Herein we described a child with a de novo 19p13.3 microdeletion, proximal to the reported cases of 19p13.3 microdeletion/duplication, with ocular manifestations of bilateral ocular colobomata complicated with microphthalmos and cataract, associated with short stature. This case highlights the phenotypic heterogeneity of deletions in the 19p13.3 region.